FAKTOR RISIKO TERJADINYA GANGGUAN FUNGSI KOGNITIF PADA PASIEN PASCA STROKE BERULANG DI RUMAH SAKIT UMUM IMELDA PEKERJA INDONESIA MEDAN TAHUN 2024 - Surya Manurung, Sarida; Nurhalimah, Nurhalimah; Manurung, Jonni Sastra (Jurnal Ilmiah Keperawatan IMELDA, 2025)
Stroke is a neurological condition that can cause impaired cognitive function. The risk of post-stroke cognitive impairment is higher in individuals who have experienced a recurrent stroke. This study aims to identify the main risk factors that contribute to impaired cognitive function in post-stroke patients. This research was conducted using qualitative descriptive research methods, the research location was carried out at the Imelda Workers Indonesia General Hospital, Medan. The research time from the start of preparing the proposal to completion was from March 2024 to August 2024. Research data was collected through in-depth interviews with participants and analyzed. The results of this research consist of 4 themes, namely: 1. (The influence of age on impaired cognitive function after a stroke). 2. (Between men and women who have the greatest potential to experience impaired cognitive function after a stroke). 3. (The patient's daily habits before experiencing impaired cognitive function after a stroke change). 4. (Is there a history of other diseases that can cause impaired cognitive function after a stroke). The conclusions from this research are: 1. Age influences cognitive function disorders after a stroke. 2. Women are more at risk of experiencing impaired cognitive function than men. 3. Activity has a big influence on impaired cognitive function after a stroke. 4. Participants' ignorance about post-stroke cognitive function disorders is increasing.